Pemberdayaan Bakat Musik Jemaat di GKE Imanuel Mandomai - Pransinartha, Pransinartha (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2024)
Gereja Kalimantan Evangelis (GKE) Imanuel Mandomai is one of the churches that has a long history in Central Kalimantan. Formerly, this church was the center of evangelism in Mandomai and has a long musical history because of its uniqueness with the trumpet and Harmonium choir. The problem encountered in this research is that the musical talents of the congregation in GKE Imanuel Mandomai have not been optimally utilized. The objective of this research is to elucidate the forms, processes, and outcomes of empowering the musical talents of the congregation at GKE Imanuel Mandomai. The research method used is descriptive qualitative method, with data collection techniques through observation, interviews and documentation. The results obtained are; there are various stages of empowering congregational musical talent using TQM implementation, including; preparation stage, planning stage and implementation stage. Besides that, empowering congregational musical talent has a positive impact on the management of music services in the church because it increases the number of musicians and the realization of the quality of music services at GKE Imanuel Mandomai.